Sistem Pemesanan Makanan dan Minuman Pada Restoran Menggunakan Teknologi NFC Berbasis Android - Putri, Annisa Yolanda; Yendri, Dodon (JITCE (Journal of Information Technology and Computer Engineering), 2018)
One area of business that is in great demand today is the culinary field. The culinary field is very mushrooming because it deals with meeting basic human needs. Therefore service to digital needs to be a concern. The goal is to improve services with NFC (Near Field Communication) based on Android for ordering food and drinks. This research uses experimental research methods by applying NFC that is on smart phones as a way to bring the smart phone closer to the NFC tag that is already on each table. Message data entered on a mini PC computer (Raspberry Pi) as the server for the next as a booking order that will be ordered by the waiter. Simulation show that a system can read NFC tags and find out table numbers via a smart phone with a 100% success rate, remote reading of NFC tags by smart phones is 2.5 cm and the average time by the system is 1,12 seconds. Besides that, the system is also equipped with calculations for payments with 100% accuracy.